The yellow book of games and energizers : playful group activities for exploring identity, community, emotions and more! - Jayaraja, ....-; Tielemans, Erwin, ....- (London : Jessica Kingsley Publishers, 2011)
People of all ages learn important life skills through playing games, and recognising this can be the key to enhancing their social, educational and personal development. Incorporating play into teaching and training not only makes learning fun, but it can also open minds to the value of cooperation, communication and reflection.The book is a collection of tried and tested games for use in workshops, youth groups and the classroom, covering everything from icebreakers and group forming ideas, to brain-bending word games like "Napoleon Has Lost His Pipe" and hilarious high energy games like "Group Juggle". With clear instructions, delightful illustrations and discussion ideas for every game, this book makes it easy to encourage everyone from age 6 to 86 to think for themselves, use their imagination, and interact positively with those around them.Packed with exciting and energizing games that will entertain everyone involved, this book will be a vital resource for teachers, youth group leaders, trainers, and anyone else wishing to enrich their work with playful games and ideas.
Keywords: Activiteiten ; groep